Developing Reading Profile of Students without using Standardised Tools: Is it Possible? - Bharti (INDIAN EDUCATIONAL REVIEW, 2014)
School students in India study three languages at the elementary level, namely mother tongue, regional language and a foreign language. The foreign language is usually English in the majority of the schools. The medium of instruction in the school could be English or Hindi (national language) or mother tongue depending on the school management and the choice of the parents. The present paper is an attempt to assess the reading errors committed by the class III students studying in a Kendriya Vidyalaya situated in the heart of the capital of India. The assessment data is compiled to create reading error profile of the class and individual students. The reading error profile provides significant information to develop remedial education programme leading to reduction of reading errors. The vital element of the entire process is the use of informal means of assessment without using the standardised reading tests.